Emerging Disease in Tilapia: Tilapia Lake Virus Disease (TiLVD) - Bunnajirakul, Sumrarn (Journal of Mahanakorn Veterinary Medicine, 2018)
Tilapia lake virus disease (TiLVD) was reported as an emerging disease in tilapia (Oreochromis spp.) in various regions of the world. TiLV is classified in Orthomyxo-like virus group. Mortality rate was found on fingerling of nile and red tilapia after cage rearing during the first month, tilapia one month syndrome was named for this loss. Affected fish revealed inflammation of the operculum and tail erosion. The developed semi-nested PCR showed more sensitivity response for detection TiLV. Restriction of fish movement, development of vaccine and TiLV resistant tilapia strains should be considered as disease control program.